The Effect of Job Training, Work Motivation, Occupational Health and Safety (K3) on Employee Performance at Cibitung Medika Hospital - Rhema Andriana Susilo; Kasmir Kasmir (International Journal Labs, 2022)
Background: Rapid business development encourages companies or organizations to optimize their human resources to face competition, especially in the health sector. This growth has led to an increase in labor demand in the health sector. Hospitals, which were previously social institutions, are now developing into an increasingly competitive service industry. Therefore, companies must have good human resources, because the progress of an organization cannot be separated from the existence and influence of human resources in it. Objective: The purpose of this study is to analyze the effect of job training, work motivation, and occupational health safety on employee performance at Cibitung Medika Hospital. Methods: This research is a quantitative study with an explanatory or causal design, and is a cross-sectional study. Results: The results obtained in the study, namely job training, had a positive and significant effect on employee performance at Cibitung Medika Hospital. Then work motivation was found to have a positive and significant effect on employee performance at Cibitung Medika Hospital. And finally, occupational safety and health have a positive and significant effect on employee performance at Cibitung Medika Hospital. Conclusion: From the results that have been obtained, it is known that job training, work motivation, occupational safety and health have a positive and significant effect on employee performance at Cibitung Medika Hospital. Regarding job training variables, it is recommended to the company that training is given continuously to each employee, it would be better if training is given from the beginning of employee placement so that employees can easily adjust to their new job.